Germany, Benelux & more. 2000-2012 [videorecording (DVD)]. - Steves, Rick, 1955- (Back Door Productions, 2009)
Includes all 7 half-hour Rick Steves' Europe TV shows on Germany, Benelux and 'Little Europe', produced from 2000 to 2009.